Communication and Language Use in the Multinational Company - Kočárová, Katarína; Pauknerová, Daniela, 1970-; Nebel, Patrick; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2016)
This Master Thesis aims to provide a clear overview about corporate communication practices and importance of a common corporate language in the multinational corporation with diversified portfolio of employees. Theoretical part introduces theoretical background which are further applied into practices in the practical part of the paper. This academic paper critically looks at a practices within a particular multinational corporation and its practical application which influences efficiency at the work place.
Vedoucí práce: Daniela Pauknerová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses